Eliminating graphene wrinkles by strain engineering. (January 2021) - Hu, Hengqian; Xia, Kailun; Zhao, Shuji; Ma, Ming; Zheng, Quanshui
Abstract: Graphene layers grown on metallic substrates by chemical vapor deposition generally exhibit wrinkles due to mismatches in thermal expansion coefficients of the graphene and the substrates, which affect remarkably the tribological, mechanical and electrical properties of graphene-based devices. Here we report an isotropic-stretching method to eliminate these wrinkles. The morphology evolution of the wrinkles during the stretching process is studied using an atomic force microscope, and a simple method for calculating the critical strain required to eliminate the wrinkles is suggested. Friction and scratching tests demonstrate that for graphene layers the friction and anti-wear performances of regions with eliminated pre-existing wrinkles are as good as the wrinkle-free regions. Our method is expected to be applicable to other layered materials grown on deformable surfaces.